THE IMPACT OF BUSINESS LEGAL REGULATIONS ON THE SECURITY AND SAFETY OF COMMERCIAL VESSELS IN INTERNATIONAL WATERS - Putri, Meyta Arinta Kartika; Aina Ilmih, Andi (Jurnal Hukum Khaira Ummah, 2024)
This study aims to examine the extent to which business legal regulations contribute to improving merchant ship safety standards in international waters and to analyze their impact on maintaining shipping safety. This study uses a normative legal approach, which focuses on the study of applicable laws as norms or guidelines in practice. The type of data used is secondary data, with data sources in the form of case studies of court decisions and literature reviews referring to related laws and regulations. The data collection method is carried out through document studies, including analysis of legal regulations, academic literature, and other official documents. Based on the study, it is concluded that business law plays a crucial role in creating a regulatory framework that supports shipping safety. Strict law enforcement against violations, including illegal fishing, not only provides a deterrent effect but also protects the country's image and natural resources. In addition, business legal regulations also have positive implications for ship safety supervision and management, including licensing, training, and certification for captains and crew. Therefore, shared responsibility between the government, operators, and service users is very important to ensure shipping safety and the sustainability of the maritime environment.